2019
DOI: 10.1021/acs.jpca.9b02115
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomeric Analysis of Chiral Isotopomers via Microwave Three-Wave Mixing

Abstract: Many achiral molecules can be made chiral by appropriate positioning of an isotope. Accurate detection of this type of chirality has remained elusive, and there is as yet no general method for detection of isotopically chiral species. Here, we present the first application of microwave three-wave mixing to isotopically chiral molecules, detecting enantiomeric excess in (R/S)-benzyl-α-D1 alcohol. Our method is expected to be applicable to a broad range of isotopically chiral molecules with a prochiral parent sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Both the assignment of absolute configuration and the measurement of the enantiomeric excess are accomplished without the need of any reference samples of the analyte. We note that a different approach to using MRR to perform chiral analysis—three‐wave mixing rotational spectroscopy [54–56] —has recently been described for molecules that are chiral by virtue of deuteration. However, in its present state of development this technique cannot assign the AC of a sample because no method has been demonstrated that can determine the absolute phase of the chiral signal.…”
Section: Discussionmentioning
confidence: 99%
“…Both the assignment of absolute configuration and the measurement of the enantiomeric excess are accomplished without the need of any reference samples of the analyte. We note that a different approach to using MRR to perform chiral analysis—three‐wave mixing rotational spectroscopy [54–56] —has recently been described for molecules that are chiral by virtue of deuteration. However, in its present state of development this technique cannot assign the AC of a sample because no method has been demonstrated that can determine the absolute phase of the chiral signal.…”
Section: Discussionmentioning
confidence: 99%
“…Kawasaki et al found that the chirality of the S and R enantiomers was mainly attributable to the very small difference between the C-D and C-H bond-lengths associated with the alpha carbon of glycine [20][21][22]. The development of a highly sensitive method for the detection of isotopic chirality in meteoritic organic compounds such as amino acids [23] with an achiral framework and isotopic enrichment therefore remains a challenging subject [24,25].…”
mentioning
confidence: 99%
“…Both the assignment of absolute configuration and the measurement of the enantiomeric excess are accomplished without the need of any reference samples of the analyte. We note that a different approach to using MRR to perform chiral analysis-three-wave mixing rotational spectroscopy [54][55][56] has recently been described for molecules that are chiral by virtue of deuteration. However, in its present state of development this technique cannot assign the AC of a sample because no method has been demonstrated that can determine the absolute phase of the chiral signal.…”
Section: Discussionmentioning
confidence: 99%